1996
DOI: 10.1002/hlca.19960790414
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation and X‐Ray Structure Analyses of (2R)‐N‐pyruvoyl‐ and (2R)‐N‐(phenylglyoxyloyl)bornane‐10,2‐sultam

Abstract: Dedicated to Prof. Vladimir Prelog on the occasion of his 90th birthday (7.111.96) ~ ~~An efficient synthesis of the two title compounds is reported, as well as their X-ray crystal-structure analyses. A discussion based on stereoelectronic considerations rationalizes the first example of a crystalline SO,/C(O) syn-periplanar conformer of a N-acylbornane-l0,2-sultam.We have recently reported the diastereoselective [4 + 2 1 cycloaddition of 1 -methoxybuta-1,3-diene to (2R)-N-glyoxyloylbornane-10,2-sultam (la)') … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the case of 2a, the O¼CÀC¼N anti-s-cis-conformation involves an intermolecular H-bond with an intercalary molecule of H 2 O [20]. For (4S,5S)-6a, both DhN and the SÀNÀC¼O dihedral angle ( Table 2) are larger than the previously reported examples (0.107 , À 17.38 [21]; 0.083 , À 9.38 [23]), and, thus, are fully consistent with the proportional correlation found for anti-conformers [24]. 5 ) For the racemic analogous ethyl ester of 8, see [25]; for racemic 9, see [26].…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In the case of 2a, the O¼CÀC¼N anti-s-cis-conformation involves an intermolecular H-bond with an intercalary molecule of H 2 O [20]. For (4S,5S)-6a, both DhN and the SÀNÀC¼O dihedral angle ( Table 2) are larger than the previously reported examples (0.107 , À 17.38 [21]; 0.083 , À 9.38 [23]), and, thus, are fully consistent with the proportional correlation found for anti-conformers [24]. 5 ) For the racemic analogous ethyl ester of 8, see [25]; for racemic 9, see [26].…”
mentioning
confidence: 68%
“…4 ) The simple presence of a heteroatom on a sp 2 -hybridized a-atom seems influential but not sufficient for imposing a SO 2 /C¼O syn-conformation [20] [21] [23]. Thus, for example, the crystalline unpublished (2R)-N-furfuroylbornane-10,2-sultam derivative exhibits an anti-conformation (DhN 0.284 ; SÀNÀC¼O 139.00(11)8; O¼CÀCÀO À 17.98(19)8), contrasting with a syn-conformation of its N-picolinoyl analogue (DhN 0.065 ; SÀNÀC¼O À 11.5(3)8; O¼CÀC¼N 128.1(2)8).…”
mentioning
confidence: 99%
“…More than a decade ago, we suggested that the syn-periplanar conformation could lead to a more reactive species in solution, and thus could eventually participate during the course of the reaction by displacing the anti/syn equilibrium 3 ) [8] [9]. This higher reactivity is believed to result from a better electronic alignment between the C¼O moiety and the N lone pair (lp), favoring delocalization on the sultam moiety through a generalized anomeric stabilization of the N lp by the anti-periplanar S¼O s* MO [2]. Indeed, we found that the DhN pyramidal height is directly correlated with the SÀNÀC¼O dihedral angle and reach local and global minima near ca.…”
mentioning
confidence: 99%
“…-Resulting from dipole interactions, N-acyl-substituted (2R)-bornane-10,2-sultam derivatives adopt essentially, in the solid state, the thermodynamically more stable SO 2 /C¼O anti-periplanar conformation 2 ). More than a decade ago, we suggested that the syn-periplanar conformation could lead to a more reactive species in solution, and thus could eventually participate during the course of the reaction by displacing the anti/syn equilibrium 3 ) [8] [9].…”
mentioning
confidence: 99%
“…This versatile N-glyoxyloyl derivative was also used for the spirocyclization of 2-substituted tryptamines [11], for Pictet-Spengler cyclization [12], for a formal synthesis of compactin and mevinolin [2] [13], and for the preparation of purpurosaminide C [14], deoxyhexoses [15], as well as [(trimethylsilyl)oxy]furan [16] and ene additions [17]. To study in more detail the scope and limitation of this kind of hetero-Diels-Alder reaction, we also recently reported the synthesis and X-ray analyses of the homologous dienophiles (À)-1b,c, obtained by direct acylation ( NaH, toluene, pyruvoyl chloride (72%) and NaH, toluene, phenylglyoxyloyl chloride (71%) [18]) of the commercially available (2R )-bornane-10,2-sultam [19]. Alternatively, (À)-1b was also obtained by ozonolysis of (2R )-N-methacryloyl-or (2R )-N-tigloylbornane-10,2-sultam ( O 3 , AcOEt, À 788, then Me 2 S (86 ± 90%) [20]) 4 ).…”
mentioning
confidence: 99%